Cytogenetic analysis of Hypomasticus copelandii and H. steindachneri: relevance of cytotaxonomic markers in the Anostomidae family (Characiformes) - Salgado, Filipe Schitini; Cunha, Marina Souza; Melo, Silvana [UNESP]; Dergam, Jorge Abdala (Pensoft Publishers, 2021)
Recent phylogenetic hypotheses within Anostomidae, based on morphological and molecular data, resulted in the description of new genera (Megaleporinus Ramirez, Birindelli et Galetti, 2017) and the synonymization of others, such as the reallocation of Leporinus copelandii Steindachner, 1875 and Leporinus steindachneri Eigenmann, 1907 to Hypomasticus Borodin, 1929. Despite high levels of conservatism of the chromosomal macrostructure in this family, species groups have been corroborated using banding patterns and the presence of different sex chromosome systems. Due to the absence of cytogenetic studies in H. copelandii (Steindachner, 1875) and H. steindachneri (Eigenmann, 1907), the goal of this study was to characterize their karyotypes and investigate the presence/absence of sex chromosome systems using different repetitive DNA probes. Cytogenetic techniques included: Giemsa staining, Ag-NOR banding and FISH using 18S and 5S rDNA probes, as well as microsatellite probes (CA)(15) and (GA)(15). Both species had 2n = 54, absence of heteromorphic sex chromosomes, one chromosome pair bearing Ag-NOR, 18S and 5S rDNA regions. The (CA)(15) and (GA)(15) probes marked mainly the subtelomeric regions of all chromosomes and were useful as species-specific chromosomal markers. Our results underline that chromosomal macrostructure is congruent with higher systematic arrangements in Anostomidae, while microsatellite probes are informative about autapomorphic differences between species.
Keywords: Anastomid; coastal basins; cytogenetics; endemic species; fluorescence in situ hybridization; freshwater fishes; repetitive sequences